ACCELERATED NODULOSIS DUE TO METHOTREXATE THERAPY IN A PATIENT WITH RHEUMATOID ARTHRITIS - Ümit Seçkin; Pınar Borman; Hatice Bodur; Özge Han; Banu Gön (Archives of Rheumatology, 2000)
We describe a patient with rheumatoid arthritis (RA) whom developed new subcutaneus nodules at right and left metacarpophalangeal joints during methotrexate (MTX) therapy in addition to the ones, on both olecranon and extensor surfaces of the left arm. Physicians treating RA patients with MTX must be avare of accelerated nodulosis as an extraarticular side effect of this drug.